Knowledge Acquisition by Means of Rough Sets Theory - Siniavskaya, Olga A.; Zhelezko, Boris A. (Pozyskiwanie wiedzy dzięki teorii zbiorów przybliżonych, 2010)
In this article possibilities of knowledge acquisition by means of rough sets theory are considered. The basic concepts of rough sets theory are given, including methods of calculation of basic indicators. Examples of rough sets theory application for calculation of probability of events' causes and consequences, estimations of results utility are described. The principle of economic information discretisation for its processing by means of rough sets theory methods is considered. Relation of rough sets theory with alternative decision-making theories and intellectual data analysis methods is shown.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 133, s. 122-130
Keywords: rough sets theory; information system; decision table; approximation; decision algorithm; knowledge acquisition